Comfortable measurement of ski-turn skill using inertial and plantar-pressure sensors - Matsumura, S.; Ohta, K.; Kimura, T. (Proceedings of the 6th International Conference on Sport Sciences Research and Technology Support - Volume 1: icSPORTS, 2018)
This paper proposes a comfortable and easy way to measure skill in ski turns with inertial and plantar-pressure sensors. The inertial sensors were used to log the motion of skis, and the plantar-pressure sensors were used to measure plantar-pressure distribution and analyze how the feet transmit force to skis. One intermediate skier and one expert skier, both adult males, participated in this experiment. They skied in short turns in six trials totally. According to the results of the experiment, the data for skidded and carved turns were clearly different. Therefore, we consider that our proposed measurement method will enable skiers to conveniently analyze their ski-turn skills on their own.